2014
DOI: 10.1142/s0218127414500989
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Bifurcations to Repetitive Spiking and Classification of Delay-Induced Bursting

Abstract: Three new routes to repetitive spiking, i.e. the delayed transcritical bifurcation, the delayed supercritical pitchfork bifurcation and the delayed subcritical pitchfork bifurcation, are revealed in this paper. We use bifurcation theory to classify bursting patterns related to three such delayed bifurcations. Then many new bursting patterns are obtained, including 24 new bursting patterns of point-point type, 27 new bursting patterns of point-cycle type and three new bursting patterns of point-torus type. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…However, from the viewpoint of fast-slow dynamics, strong and weak excitations are nothing special. The reason for this is that the slow variables are cos(ω 1 t) and cos(ω 2 t) and both amplitudes β 1 and β 2 belong to the fast subsystem, i.e., like other parameters in the fast subsystem, β 1 and β 2 are general parameters of the fast subsystem, e.g., see the fast subsystems ( 9)- (11). No matter what the magnitudes of the amplitudes are, the amplitudes can change qualitatively properties of the MMOs as long as they vary and pass through bifurcation points of the fast subsystem.…”
Section: General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from the viewpoint of fast-slow dynamics, strong and weak excitations are nothing special. The reason for this is that the slow variables are cos(ω 1 t) and cos(ω 2 t) and both amplitudes β 1 and β 2 belong to the fast subsystem, i.e., like other parameters in the fast subsystem, β 1 and β 2 are general parameters of the fast subsystem, e.g., see the fast subsystems ( 9)- (11). No matter what the magnitudes of the amplitudes are, the amplitudes can change qualitatively properties of the MMOs as long as they vary and pass through bifurcation points of the fast subsystem.…”
Section: General Methodsmentioning
confidence: 99%
“…It has also been shown that a slowly varying periodic parameter can stabilize unstable orbits [9], annihilate one of the coexisting states, and thus results in controlled monostability [10]. In particular, a slowly varying periodic parameter can lead to periodic bifurcation delay behaviors, which have been identified as new routes to repetitive spiking and bursting [11]. However, most of the previous work focused on systems with a single slowly varying periodic parameter and there has been little work done on the analysis of dynamical systems with two slowly varying control parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [21] explored multiple fast-slow motions, including "periodic bursts with quasi-periodic spiking", "torus/short transient" mixed mode oscillations, "pitchfork/long transient" periodic mixed mode oscillations, amplitude-modulated and irregular oscillations from numerical method. It can be seen that the behaviors of the mixed-mode oscillation can be produced by many factors, such as different kinds of bifurcation structures [22,23], delay behaviors [24,25], and hysteresis loops [26,27]. However, most of the results about mixed-mode oscillations are made for smooth systems.…”
Section: Introductionmentioning
confidence: 99%
“…F 1 F 1 > 0 ð Þis the unmodulated forcing amplitude, and F 2 F 2 > 0 ð Þ is the degree of forcing modulation, X X > 0 ð Þ is the forcing frequency, and x x > 0 ð Þis the modulation frequency. Hysteretic cycles can emerge in the reduced form of equation 1analyzed by the singular perturbation methods, [27][28][29][30] given by…”
Section: Introductionmentioning
confidence: 99%
“…Hysteretic cycles can emerge in the reduced form of equation (1) analyzed by the singular perturbation methods, 2730 given by where Ω true(0<Ω1true). Equation (2) may exhibit the typical fast–slow oscillations as shown in Figure 1, where the fixed parameters are fixed at a=b=1, F1=1, and Ω=0.01 (throughout the paper, we denote truex˙ as y).…”
Section: Introductionmentioning
confidence: 99%